Efficient Java Communication Protocols on High-speed Cluster Interconnects - Taboada, G.L.; Tourino, J.; Doallo, R. (Proceedings. 2006 31st IEEE Conference on Local Computer Networks, 2006)
This paper presents communication strategies for achieving efficient parallel and distributed Java applications on clusters with high-speed interconnects. Communication performance is critical for the overall cluster performance. Previous efforts at obtaining efficient Java communications have a limited applicability on high-speed interconnects as they are focused on high level APIs like RMI, ignoring the particularities of these systems and their native high performance communication protocols. By relying on a custom Java socket implementation higher degrees of performance can be achieved exploiting high-speed interconnect facilities. Several protocol definitions are presented, looking for obtaining high performance Java communications. Moreover, the quality of the protocol implementations and their design decisions has been thoroughly evaluated on a scalable coherent interface (SCI) and gigabit Ethernet (GbE) testbed cluster. The results of this analysis have demonstrated that these Java protocols obtain similar results to native communications